2019
DOI: 10.3892/ol.2019.10552
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an insufficient radiofrequency ablation orthotopic nude mouse model of hepatocellular carcinoma to study the invasiveness and metastatic potential of residual cancer

Abstract: In order to assess the metastatic potential of residual hepatocellular carcinoma (HCC) following insufficient radiofrequency ablation (RFA) and to improve the current animal model, an insufficient RFA orthotopic nude mouse model of HCC was developed in the present study. A human HCC orthotopic nude mouse model was established using HCCLM3 cells, which has a high metastatic potential, labeled with green fluorescent protein. A total of 12 nude mice within the RFA group received insufficient RFA and 12 mice in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In recent years, many kinds of research have manifested the potent advantages of minimally invasive ablation for liver tumors [32][33][34]. However, of note, ultrasoundguided thermal ablation enables locoregional treatment for hepatic tumors, but with the weaknesses of recurrent residual tumors and inferior outcomes caused by incomplete ablation [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many kinds of research have manifested the potent advantages of minimally invasive ablation for liver tumors [32][33][34]. However, of note, ultrasoundguided thermal ablation enables locoregional treatment for hepatic tumors, but with the weaknesses of recurrent residual tumors and inferior outcomes caused by incomplete ablation [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the factors such as tumor size, location, and liver function, complete ablation is often not possible. Recently, a growing number of studies have shown that residual tumors progress more rapidly after incomplete ablation ( 2 , 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor animal models. Tumor animal models have been widely used in the study of molecular mechanisms of tumor genesis and development (34,35).…”
Section: Common Research Objects Of Tumor Hyperthermiamentioning
confidence: 99%